PELATIHAN OXYTOCIN MASSAGE BAGI PENDAMPING IBU NIFAS - Nurus Safa'ah; Dyah Pitaloka; Tiara Putri Ryandini (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2022)
Lack of milk production in the first days after giving birth is caused by a lack of stimulation of the hormone prolactin and the hormone oxytocin. Decreased milk production is caused by decreased stimulation of the hormones prolactin and oxytocin. Efforts that can be made to stimulate an increase in the hormones prolactin and oxytocin include early initiation of breastfeeding, expressing breast milk and performing oxytocin massage, while breast care for postpartum mothers is less effective and efficient in increasing breast milk production. In Indonesia (Kemenkes, 2018) the coverage of infants who were exclusively breastfed in 2018 was 68.74%. In 2018, East Java got 77.51%, and especially in Tuban Regency (Tuban District Health Service data) in the same year it got 73.85%, then in 2019 it increased to 79.6%. However, in 2020 there was a decline to 76.93% of infants who were exclusively breastfed. Based on the data above, it shows that the success of exclusive breastfeeding is still not getting optimal results.Oxytocin massage training has never been carried out in Tegalagung Village, especially for breastfeeding companions such as Posyandu cadres, husbands or families. The method used in this community service activity is the method of lectures, discussions, simulations and demonstrations using leaflets and audio-visual media. The number of postpartum mothers who participated in the training was 20 people.The results of training activities for postpartum women assistants in the village of Tegalagung showed that the results of knowledge analysis showed that overall there was an increase in participants' knowledge after attending the training, meaning that there was an influence on increasing the knowledge of postpartum women assistants after participating in oxytocin massage training. So it was concluded that there was an increase in knowledge between before and after training about oxytocin massage.Recommended that health workers need to consistently and continuously provide training to postpartum mother companions (husband, family or cadres) in order to assist the process of behavioral change in postpartum mothers to exclusively breastfeed and provide care during the postpartum period.